How Do Organizational Visibility, Regulation, And Energy Use Shape The Future Of Green Finance? A Systematic Review - Erdapuspita, Zsa Zsa Ilmanabilah; Sukmadilaga, Citra; Tanzil, Nanny Dewi (JURNAL MANAJEMEN MOTIVASI, 2025)
The aim of this study is to review publications on green finance between 2020 and 2025 using a systematic literature review (SLRs). Using the PRISMA protocol, 66 relevant articles were sourced from the Scopus database, identified through keywords including "green finance", "organizational visibility", "regulation", "policy", and "energy use". A network analysis using VOSviewer was conducted to visualize keyword co-occurrences and citation trends, revealing visibility, regulation, and energy consumption as dominant and interconnected themes. The study highlights that organizational visibility, strengthened by public disclosure and stakeholder pressure, significantly influences firms' engagement in green financial practices. Regulatory frameworks are found to be essential in shaping green investment behavior, particularly through incentives, reporting mandates, and policy enforcement. Meanwhile, energy use especially in high-emission sectors is identified both as a key driver and a target of green finance strategies. The analysis also identifies challenges such as inconsistent regulatory standards, limited data integration, and technological readiness, which hinder the scalability of green finance. The study underscores the importance of harmonized policies, improved transparency, and the integration of digital tools to support effective green capital flows. This research affirms the critical role of visibility, regulation, and energy transition in advancing green finance and provides a comprehensive foundation for future studies aiming to enhance the impact of sustainable financial ecosystems globally.